An Assessment of Geo-Political Representation of Women in the 2023 Elections in Nigeria: The Role of the Media - AKINDUTIRE, Ayomide Samson; ADEBUSUYI, Adedotun (The Gender Truth Journal, 2025)
Ethnic diversity and gender equity are critical dimensions of inclusive democratic governance. Political participation of women in Nigeria remains disproportionately low, with significant variations influenced by ethnicity. This study examines the ethnic representation of women in Nigerian politics, using both primary and secondary data. The research content analyzes quantitative data from secondary data obtained from the Independent Electoral Commission and research literature on women’s participation in politics across the six zones. The findings reveal that ethnic identity significantly influences women’s access to political opportunities, with women from the North West and North East groups facing compounded challenges due to cultural expectations, religious expectations, financial constraints, and limited political networks. Those involved are mostly not at the same level of education as compared with females from the South-west, South-east, and South-south. The North Central provided profound evidence for this study due to its mixed ethnic and cultural heritage. There are more female contestants in the North Central when compared to other Northern Zones. The study finds that women who win elections in Nigeria are above 50 years of age, who have demonstrated proven political and strong financial stands, which align with the elite theory. Though the research revealed that religion is not one of the major factors influencing women’s participation in politics in Southern Zones. Also, 28 of the contestants at the senatorial level have degrees or attended higher education. Worthy of note is the South East, which has 3 PhD degree candidates. Generally, South-south has proven to have encouraged female contestants at all levels, considering the fact that 33 female contestants from the age of 35 years and above contested, when compared to other geopolitical zones.